Implementasi Kebijakan Pemekaran Terhadap Kualitas Pelayanan Kesehatan Di Kabupaten Mamasa Sulawesi Barat - Lambali, Suryadi; Rizal, Muhammad; Ismail, Nuralamsyah; Fauzi, Rizal (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2022)
This study aims to analyze and empirically test the fragmentation of policy implementation on the quality of health services in Mamasa District, West Sulawesi, research question is how much the effect of policy implementation fragmentation to quality health service in Regency of Mamasa in West Sulawesi. The Method in this Research used analyses quantitative with model of path analysis. Data obtained by through circulating of questionnaire to all policy implementor fragmentation and cervices health in Regency of Mamasa. The Result of research to found that execution of policy implementation fragmentation as according to variabel exogen that is communications, resource, disposition or attitude, and the bureaucratic structure, and so that quality health service have as according to reliability, responsiveness, assurance, empathy, and tangible. The correlation influence of policy implementation fragmentation to quality health service, hence did not all of dimension from policy implementation fragmentation have an effect on significant to quality health service, so that create new models is to called as model struktur-3 where only have dimensions of resources, disposition or attitude, and structure of bureaucracy having an effect on significant. From model of this struktur-3 to created a model of policy implementation fragmentation can be influenced by consistency factor, authority, facilities, staffing the bureaucracy, incentive, and system operating procedure. Apart from the internal factor is influenced by environmental factor related to existence of conflict potency, leadership, elite figure, and the local culture.